Long-term evaluation of dabigatran 150 vs. 110 mg twice a day in patients with non-valvular atrial fibrillation - Ezekowitz, Michael D.; Brückmann, Martina (Europace, 2016)
Aims: The Randomized Evaluation of Long-Term Anticoagulation Therapy (RE-LY) trial allowed patients who completed the trial receiving their assigned dabigatran 150 mg (D150) or 110 mg (D110) twice a day to continue into the Long-term Multicenter Extension of Dabigatran Treatment in Patients with Atrial Fibrillation (RELY-ABLE) trial. This permitted assessment of outcomes over a median of 4.6 and a maximum of 6.7 years, respectively. Methods and results: The analysed population included only those patients who completed RE-LY on dabigatran and continued into RELY-ABLE without interruption of assigned dabigatran. Cumulative risk was expressed as Kaplan-Meier plots. Outcomes were compared using Cox proportional hazard modelling. Stroke or systemic embolization rates were 1.25 and 1.54% per year (D150 and D110, respectively); hazard ratio (HR) 0.81 [95% confidence interval (CI): 0.68-0.96] (P = 0.02). Ischaemic stroke was 1.03 (D150) and 1.29%/year (D110); HR 0.79 (95% CI: 0.66-0.95) (P = 0.01). Haemorrhagic stroke rates were 0.11 (D150) and 0.13%/year (D110); HR 0.91 (95% CI: 0.51-1.62) (P = 0.75). Rates of major haemorrhage were 3.34 (D150) and 2.76%/year (D110); HR 1.22 (95% CI: 1.08-1.37) (P = 0.0008). Intracranial haemorrhage rates were 0.32 (D150) and 0.23%/year (D110); HR 1.37 (95% CI: 0.93-2.01) (P = 0.11). Mortality was 3.43 (D150) and 3.55%/year (D110); HR 0.97 (95% CI: 0.87-1.08) (P = 0.54). Conclusion: Annualized rates of all outcomes were constant with better efficacy of D150, less major bleeding with D110, and low intracerebral haemorrhage rates for both doses. There were no additional safety concerns. This is the longest continuous randomized experience of a novel anticoagulant.